Climate Village sustainability and institutional support: A systematic review - Syafrial, Syafrial; Febriamansyah, Rudi; Mahdi, Mahdi; Zamzami, Lucky (Sustinere: Journal of Environment and Sustainability, 2025)
This study presents a systematic literature review (SLR) of climate village programs, with particular attention to institutional support, community participation, and sustainability practices. Guided by the PRISMA protocol, 42 eligible articles were analyzed to map the geographical scope, journal quality, theoretical frameworks, governance arrangements, and the role of local resources. The review reveals significant heterogeneity across contexts: African studies emphasize renewable energy, Bangladesh highlights adaptation politics, Indonesia adopts a multi-sectoral approach, while small island states prioritize coastal conservation. Most studies employ qualitative and participatory methods, drawing on resilience theory, socio-ecological systems, participatory governance, and energy transition perspectives. Institutional support is found to operate through multi-level governance involving government, NGOs, communities, and private actors. However, power asymmetries often constrain long-term sustainability. Local resources and indigenous knowledge emerge as critical for resilience but require supportive legal and institutional frameworks to avoid elite capture and ensure genuine empowerment. Theoretically, this review advances the concept of Climate Villages as socio-ecological laboratories linking global climate agendas with local action. Practically, it identifies the need for contextualized interventions, stronger governance coordination, and knowledge co-production. The findings provide actionable insights for policymakers, practitioners, and researchers seeking to strengthen the design, implementation, and sustainability of Climate Village initiatives.